The Effect of Interpersonal Communication on Employee Performance with Emotional Intelligence as a Moderating Variable - Luni Anugrahni (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – The purpose of this research is to examine how effective interpersonal communication influences worker productivity, with the inclusion of EQ as a moderating variable.Design/Methodology/Approach – This study used a saturating sample size of 37 people from the Perum Bulog Regional Office in Central Kalimantan as its unit of analysis. SmartPLS 3.0 was used to perform a Likert-scale analysis of the gathered data.Findings - The results of this study concluded that the Interpersonal Communication A variable has a significant effect on the Employee Performance of the Bulog Regional Office of the Central Kalimantan Regional Office. While the Emotional Intelligence Variable has no significant effect on strengthening the relationship between Interpersonal Communication on the Employee Performance of Bulog Regional Office in Central Kalimantan.